Multimedia Steganography Based on Least Significant Bit (LSB) and Duffing map - Jinan N. Shehab; Haraa Raheem Hatem (Journal of Madenat Alelem University College, 2016)
This paper presents hiding the text or image (secret information) inside other image (cover image) based on Least Significant Bits (LSB). The position of characters in original secret text and the position of pixels in original secret image have been changed by Duffing map (random number generator). The fundamental idea is to insert the secret message ( text, gray image and color image) in the least significant bits of the cover image (gray or color image). This actually works because the Human Visual System (HVS) is not sensitive enough to pick out changes in color. The experiments and comparative studies show that the algorithms are characterized by many features of the ability of hiding huge data, and then the ability of extracting secret message without errors. Beside the return image, has efficacies (to human acquaintance) according to peak signal to noise ratio (PSNR) and mean square error (MSE), also retain both the explicitness and the characteristics of the both secret message and cover image.